The Effect of Implementing the CoCoAER and Jigsaw Learning Models on Enhancing Students' Understanding of Concepts in Static Fluid (Jurnal Pendidikan Fisika, 2025)
The increasing complexity of physics learning in the Industrial Revolution 4.0 era demands innovative pedagogical strategies to address students’ conceptual difficulties, particularly in abstract topics like static fluid. Misconceptions about hydrostatic pressure remain prevalent due to traditional, non-contextual instructional approaches. This study aims to compare the effectiveness of two cooperative learning models CoCoAER and Jigsaw in improving students’ conceptual understanding of static fluid and to examine students’ perceptions of both methods. A quasi-experimental design with a non-equivalent control group was applied to 90 eleventh-grade students at MAN 3 Banda Aceh, divided into CoCoAER, Jigsaw, and conventional lecture groups. Data were collected through pre-and post-tests and student response questionnaires. Results from ANOVA and N-Gain analysis indicated that the CoCoAER model significantly outperformed both the Jigsaw and lecture models (p < 0.05), with 73.3% of students showing high improvement and an average post-test score of 86. Students' satisfaction also favored CoCoAER, with 96% indicating a “very satisfied” rating, compared to 50% and 40% for Jigsaw and conventional methods, respectively. The novelty of this study lies in applying the CoCoAER model to fluid dynamics, integrating contextual learning, collaboration, and error anticipation strategies. In conclusion, the CoCoAER model offers a highly effective and student-centered approach to teaching static fluid, contributing to the reduction of misconceptions and enhancing physics learning outcomes.